Lincoln and the Bluegrass : slavery and Civil War in Kentucky - Townsend, William H. (William Henry), 1890-1964 (University Press of Kentucky, 1955)
The Bluegrass region of Kentucky was the only part of the slaveholding South Abraham Lincoln knew intimately. How the cultural environment of Lexington, the home of Lincoln's wife, with its pleasure-loving aristocracy, its distinguished political leaders, and its slave auctions shaped his opinions on slavery and secession is traced in these pages. In this city, early known as the ""Athens of the West, "" Lincoln's alliance with the Todd family widened his circle of acquaintances to include such diverse personalities as the fiery Cassius M. Clay, who urged immediate emancipation; Dr. Robert J. Br.